GE_GERICHTE C/3776/2012 vom 6. Mai 2016 - GE Cour de justice (2016)
LIBRE APPRÉCIATION DES PREUVES ; ERREUR ESSENTIELLE ; DOL(VICE DU CONSENTEMENT) ; CULPA IN CONTRAHENDO | CO.20.2; CO.23; CO.24.1.4; CO.24.2; CO.28.1; CPC.157;